Relationship Between Masticatory Muscle Size and Bone Regeneration After Mandibular Angle Osteotomy. Issue 8 (November 2021) - Huang, Yuanliang; Yang, Liya; Lin, Yanxian; Mu, Lin; Zhao, Minghao; Ma, Xiaoyang; Teng, Li
Abstract : Abstract: Mandibular angle osteotomy with outer cortex grinding has become the preferred cosmetic procedure for correcting square faces. After surgery, bone hyperplasia at the mandibular angle affects the operation result. This study evaluated the effect of the masticatory muscles on bone repair. From January 2016 to January 2019, patients who underwent mandibular angle osteotomy with outer cortex grinding were retrospectively reviewed. Computed tomography data of these patients were collected, and the bone volume of the mandibular angle changes and its correlation with masticatory muscle morphology were analyzed. Computed tomography data measurement results showed that a large amount of bone in the mandibular angle area was removed by the operation; however, the long-term follow-up results showed that there was bone hyperplasia in the mandibular angle areas. Compared with the immediate postoperative bone volume, the difference was statistically significant ( P < 0.01). The thickness and cross-sectional area of the masseter muscle were significantly related to bone regeneration ( P < 0.01). This study suggests that mandibular angle osteotomy with outer cortex grinding could ablate the symptoms of a prominent mandibular angle; however, muscle-related bone hyperplasia in the mandibular angle area after surgery was a non-negligible event, which may significantly compromise surgical outcomes. Abstract : Supplemental Digital Content is available in the text